JĘZYKOZNAWSTWO KOGNITYWNE A ROZWIJANIE KOMPETENCJI MIĘDZYKULTUROWEJ W KONTEKŚCIE UMIĘDZYNARODOWIENIA SZKOLNICTWA WYŻSZEGO W POLSCE - Strugielska, Ariadna (Neofilolog, 2018)
The article demonstrates possible impact of internationalization at Polish universities on the ways in which research interests can be polarized and intercultural competence fostered. Since international educational programs tend to be created by academics whose interest in intercultural competence is secondary, i.e. it derives from the process of internationalization. The perspectives of various research domains are likely to influence concepts of intercultural competence and the ways of its development. Simultaneously, academic interests of lecturers will be polarized by intercultural and international contexts. The said phenomenon is illustrated with examples from an Erasmus+ seminar at the NCU in Poland.